Male Infertility Problem: A Contemporary Review on Present Status and Future Perspective. (8th August 2019) - Dissanayake, D. M. I. H.; Keerthirathna, W. L. R.; Peiris, L. Dinithi C.
Semen quality plays a pivotal role in maintaining healthy fertilizing ability of spermatozoa. Male infertility is a rising global problem with an increasing declining in male semen quality among men living in Africa, Europe, North American, and Asia. Though the sperm acquire proactive mechanisms during spermatogenesis and their epididymal maturation, they still remain viable for toxic insult. Declining semen quality is a major contributor to infertility. Studies have postulated that different factors, such as exposure to pesticides, industrial chemicals, heavy metals, obesity, alcoholism, tobacco smoking, sedentary lifestyles, poor nutrient intake, oxidative stress, physiological factors, genetic factors can influence male fertility. Routine semen analysis and assays for sperm chromatin integrity are the most widely utilized and best studied adjunctive diagnostics in male infertility. Over the years, scientists have developed different treatment options for male infertility. Male infertility with known etiology can be treated successfully, but other causes like genetic factors require pragmatic approaches. This article summarizes protective mechanisms of spermatogenesis, causes, diagnosis, and both modern and traditional treatment approaches of male infertility. Further, this article highlights present issues and direction for future exploration of the male infertility problem.